SOCIALIZATION OF DEFAMATION THROUGH SOCIAL MEDIA UNDER THE ITE LAW - Riza Cadizza; Affifuddin Affifuddin (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2024)
With the increasing ease of accessing and sharing information through social media, there is a greater possibility of individuals unknowingly getting caught up in the Electronic Information and Transactions Act if they are unaware of the rules governing comments, feedback, or criticism on social media. This socialization aims to raise awareness among students at a high school located in Banda Aceh, encouraging them to use social media more responsibly to avoid falling afoul of the ITE Act. The results of the socialization effort have revealed that the students have some knowledge that there are limitations when it comes to writing or commenting on social media, but they are unaware of the specific regulations, which, if violated, could lead to imprisonment for the offenders.   Keywords: Socialization, social media, Act